2008
DOI: 10.1177/0309132508090980
|View full text |Cite
|
Sign up to set email alerts
|

Childhood and the politics of scale: descaling children's geographies?

Abstract: The past decade has witnessed a resurgence of interest in the geographies of children's lives, and particularly in engaging the voices and activities of young people in geographical research. Much of this growing body of scholarship is characterized by a very parochial locus of interest — the neighbourhood, playground, shopping mall or journey to school. In this paper I explore some of the roots of children's geographies' preoccupation with the micro-scale and argue that it limits the relevance of research, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 315 publications
(171 citation statements)
references
References 97 publications
7
162
0
2
Order By: Relevance
“…13 common knowledge (e.g. Vanderbeck and Dunkley 2004;Wridt, 2004;Kallio 2007;Ansell 2009). To understand the variable meanings of the everyday it is necessary to retain theoretical openmindedness towards the many forms, arenas, starting points, and foci of children's political agencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 common knowledge (e.g. Vanderbeck and Dunkley 2004;Wridt, 2004;Kallio 2007;Ansell 2009). To understand the variable meanings of the everyday it is necessary to retain theoretical openmindedness towards the many forms, arenas, starting points, and foci of children's political agencies.…”
Section: Discussionmentioning
confidence: 99%
“…Vanderbeck 2008; Ansell 2009;Kallio and Häkli 2013). However, in empirical terms, certain geographies have received more attention than others during the past three decades, providing fruitful starting points for further theorization and methodological work.…”
Section: Geography In Children's Politicsmentioning
confidence: 99%
“…This tradition of work has been open to the critique that it produced an overwhelming emphasis on different children's micro-geographies at the expense of a macro analysis (Ansell 2009). However, it is crucial to note that geographers' engagement with ideas about spatiality, and our strong heritage of feminist thinking, helped us to avoid the worst of the dualist split between either global (social structural/ minority group) or local (socially constructed/tribal child) modes of thinking; a split which, like the nature/culture divide, did indeed hamper the new paradigm in other disciplinary contexts (James, Jenks, and Prout 1998;Holloway and Valentine 2000a).…”
Section: Children's Voices and The Issue Of Agencymentioning
confidence: 99%
“…Extensive research in children's geographies has demonstrated the significance of space and place for young people's experiences and identities (Ansell 2009;Skelton 2009). Spatially structured political-economic processes produce spatially uneven lifechances (Katz 2004;Ruddick 2003).…”
Section: Space Time and Time-space In Young Livesmentioning
confidence: 99%